Perspectives on Microbial Electron Transfer Networks for Environmental Biotechnology - Zhou, Shaofeng; Song, Da; Gu, Ji-Dong; Yang, Yonggang; Xu, Meiying (Frontiers in Microbiology, 2022)
The overlap of microbiology and electrochemistry expands plenty of opportunities for deeper understandings of the redox biogeochemical cycle of natural-abundant elements (like iron, nitrogen, and sulfur) on Earth. The electroactive microorganisms (EAMs) mediate electron flows outward cytomembrane via diverse pathways like multiheme cytochromes, bridging an electronic connection between abiotic and biotic reactions. On an environmental level, decades of research on EAMs and the derived subject termed “electromicrobiology” provides a rich collection of multidisciplinary knowledge and establishes various bioelectrochemical designs for the development of environmental biotechnology. Recent advances suggest that EAMs actually make greater differences on a larger scale, and the metabolism of microbial community as well as ecological interactions between microbes plays a great role in the bioremediation processes. In this perspective, we propose the concept of microbial electron transfer networks (METN) that demonstrates more on the “species to species” interactions, discuss several key questions ranging from cellular modification to microbiome construction. Future research directions including metabolic flux regulation and microbes-materials interactions are also highlighted to advance understanding of METN for development of next-generation environmental biotechnology.